2018
DOI: 10.1056/nejmoa1804093
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dupilumab in Glucocorticoid-Dependent Severe Asthma

Abstract: In patients with glucocorticoid-dependent severe asthma, dupilumab treatment reduced oral glucocorticoid use while decreasing the rate of severe exacerbations and increasing the FEV. Transient eosinophilia was observed in approximately 1 in 7 dupilumab-treated patients. (Funded by Sanofi and Regeneron Pharmaceuticals; LIBERTY ASTHMA VENTURE ClinicalTrials.gov number, NCT02528214 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
771
5
61

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 917 publications
(873 citation statements)
references
References 24 publications
36
771
5
61
Order By: Relevance
“…For several years, omalizumab was the only broadly applied biological in allergic diseases in childhood and adult asthma and chronic urticaria . Recently, phase III trials demonstrated efficacy by blocking the IL‐4/IL‐13 pathway in glucocorticoid‐dependent severe asthma, moderate‐to‐severe uncontrolled asthma, CRSwNP, and atopic dermatitis (dupilumab), by blocking IL‐5 in severe eosinophilic asthma (mepolizumab, reslizumab) and CRSwNP and severe uncontrolled asthma by blocking the IL‐5 receptor (benralizumab) . FDA and EMA approved mepolizumab, reslizumab, and benralizumab for adult uncontrolled asthma and dupilumab for atopic dermatitis in adolescents and adults, and these biologics are integrated in current guidelines and position papers .…”
Section: Unmet Needs and Future Research Areas In Treatment Of Allergmentioning
confidence: 99%
“…For several years, omalizumab was the only broadly applied biological in allergic diseases in childhood and adult asthma and chronic urticaria . Recently, phase III trials demonstrated efficacy by blocking the IL‐4/IL‐13 pathway in glucocorticoid‐dependent severe asthma, moderate‐to‐severe uncontrolled asthma, CRSwNP, and atopic dermatitis (dupilumab), by blocking IL‐5 in severe eosinophilic asthma (mepolizumab, reslizumab) and CRSwNP and severe uncontrolled asthma by blocking the IL‐5 receptor (benralizumab) . FDA and EMA approved mepolizumab, reslizumab, and benralizumab for adult uncontrolled asthma and dupilumab for atopic dermatitis in adolescents and adults, and these biologics are integrated in current guidelines and position papers .…”
Section: Unmet Needs and Future Research Areas In Treatment Of Allergmentioning
confidence: 99%
“…However, dupilumab, which targets the IL4 receptor preventing IL‐4 and IL‐13 signalling, demonstrated a significant reduction in severe exacerbations (47.7% reduction for 200 mg dupilumab compared to placebo, P < 0.001) and additionally demonstrated lung function improvement which was evident early after treatment initiation (at week 12, FEV 1 increased 0.14 litres compared to placebo, P < 0.001) . Dupilumab treatment also resulted in a significant reduction in OCS in subjects on maintaining OCS treatment (70.1% with dupilumab vs 41.9% in the placebo group [ P < 0.001] with a 59% lower exacerbation rate than placebo and mean increase in FEV1 of 0.22 litres more than placebo) …”
Section: Recent Novel Therapeutic Advancesmentioning
confidence: 99%
“…In the last phase 3 VENTURE study, 210 teenagers (aged ≥12 years) and adults with oral glucocorticoid‐treated asthma received 300 mg of add‐on dupilumab treatment every 2 weeks for 24 weeks. This study showed the efficacy of dupilumab on the reduction of OCS treatment (−70.1% in the dupilumab group vs −41.9% in the placebo group), with 48% of the patients completely discontinuing OCS in the dupilumab group.…”
Section: Other Biologics Which Could Be Of Interest In Children With mentioning
confidence: 99%